Regional Government Policy Analysis against Coaching and Development of Physical and Physical Education Teacher for Junior High School in West Sumbawa Regency (Journal of Physical Education and Sports, 2018)
The purpose of this study was to analyze local government policies on the development and development of sports and health physical education teachers in West Sumbawa Regency. This study uses a qualitative approach. The methods used are interviews, observations, and documentation. The subjects of this study were government agencies including Commission I DPRD, Department of Youth and Sports Education and Chairperson of MGMP Physical education Junior High School. Data is analyzed by triangulating data. The results of this study indicate that the local government policy on coaching and development of sports physical and health education teachers for Junior High School in West Sumbawa regency is seen in terms of policy program activities in improving teacher coaching and development in the form of activity programs contained in the Management Official Decree West Sumbawa Regency Regional Finance Number 23 of 2017 "Regarding the approval of the budget for the implementation of the regional work unit (DPA-SKPD) Department of Department of Youth and Sports Education West Sumbawa Regency's. Conclusions from the results of the research on local government policy on coaching and development of sports physical and health education teachers for Junior High School in West Sumbawa Regency have generally existed in general but specifically for coaching and development of sports and health physical education teachers do not yet exist. Therefore, it is hoped that the local government should make local regulations (PERDA) which regulates the policy on coaching and development teachers of sports physical education and health Junior High School in West Sumbawa Regency.